Holotomography versus X-ray grating interferometry: A comparative study - Zanette, I.; Lang, S.; Rack, A.; Dominietto, M.; Langer, Max; Pfeiffer, F.; Weitkamp, Timm; Mueller, B. (Applied Physics Letters, 2013)
X-ray phase-contrast imaging techniques are used at synchrotron facilities to visualize tiny density variations in bulk samples. They overcome the limitations of other non-destructive methods, which often provide insufficient spatial and/or density resolution. Holotomography (HT) and X-ray grating interferometry (XGI) are among the most powerful phase-contrast techniques. Here, we show a direct comparison of HT versus XGI. We find that XGI excels in fidelity of the density measurements and is more robust against low-frequency artifacts, while HT is superior in spatial resolution. This study gives indications for applications and developments of phase-contrast imaging. © 2013 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-08